Creating a Sustainable Interdisciplinary Humanities Department - Lucia Ortiz; Kate Edney; Raffaele Florio (Academic Chairpersons Conference Proceedings, 2017)
A trend at smaller colleges and universities is reconfiguring several small departments into a single, larger department. The leadership team—undergraduate chair, graduate program director, associate dean—of a Department of Humanities in its second year, will discuss the lessons learned over one year of breaking down silos across disciplines and degree levels.
Keywords: Humanities; Social Sciences; Consolidation; Collaboration; Interdisciplinarity